2008
DOI: 10.1007/s10488-008-0176-9
|View full text |Cite
|
Sign up to set email alerts
|

Results of an Innovative University-based Recovery Education Program for Adults with Psychiatric Disabilities

Abstract: This study examined the effectiveness of an educational approach to psychiatric rehabilitation called the Recovery Center. Using a quasi-experimental design we recruited 97 intervention and 81 comparison participants and examined the intervention's impact on health, mental health, subjective, and role functioning outcomes. Results suggested that this intervention was effective in improving subjective outcomes, especially empowerment and recovery attitudes, both of which received primary emphasis in the interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 44 publications
5
35
0
Order By: Relevance
“…This suggests that the center aligns well with newer incarnations of recovery centers that emphasize the importance of education and functional recovery over and above clinical recovery (2,3,6,7) In line with other recent research, this study affirmed the feasibility and popularity of recovery centers that focus on educational and functional improvement (2,6,7). However, the high proportion of time devoted to such activities and the strict school-like atmosphere make Pathways Resource Center somewhat distinct from these older models.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This suggests that the center aligns well with newer incarnations of recovery centers that emphasize the importance of education and functional recovery over and above clinical recovery (2,3,6,7) In line with other recent research, this study affirmed the feasibility and popularity of recovery centers that focus on educational and functional improvement (2,6,7). However, the high proportion of time devoted to such activities and the strict school-like atmosphere make Pathways Resource Center somewhat distinct from these older models.…”
Section: Discussionsupporting
confidence: 87%
“…It was similar to a popular and effective recovery center in Boston described by one of the few previous studies of recovery centers (6,7). It was similar to a popular and effective recovery center in Boston described by one of the few previous studies of recovery centers (6,7).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…40 It has also been used in the assessment of recovery and rehabilitation-based interventions, treatments and programmes. [41][42][43] As a clinical outcomes measure, BASIS-32 can be used to establish the validity of I.ROC as an outcome measure more broadly in line with routine outcome measurement.…”
Section: Methodsmentioning
confidence: 99%
“…This is an area requiring further research, including peer-reviewed studies. However, several shorter-term international studies 13 have demonstrated that many students gain numerous benefits that include: * an improved sense of identity and empowerment * increased feelings of hopefulness * has staff who become coaches who help people find their own solutions * maintains power imbalances and reinforces the belief that all expertise lies with the professionals * lets students choose their own courses, work out ways of making sense of (and finding meaning in) what has happened and become experts in managing their own lives * a greater sense of purpose and direction * increased knowledge about, and awareness of, their own determinants of mental well being * Reduced need for professional mental health services and reduced hospitalisations * skills and learning about their mental well being that contribute to increased self-mastery and coping strategies * specific knowledge about housing and personal welfare * specific skills and knowledge leading to employment and further mainstream education. 14…”
Section: Benefits Of Rcsmentioning
confidence: 99%